2009
DOI: 10.5479/si.01960768.38.1
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the Smithsonian Marine Science Symposium

Abstract: s m i t h s o n i a n c o n t r i b u t i o n s t o t h e m a r i n e s c i e n c e s • n u m b e r 3 8 SERIES PUBLICATIONS OF THE SMITHSONIAN INSTITUTIONEmphasis upon publication as a means of "diffusing knowledge" was expressed by the fi rst Secretary of the Smithsonian. In his formal plan for the Institution, Joseph Henry outlined a program that included the following statement: "It is proposed to publish a series of reports, giving an account of the new discoveries in science, and of the changes made from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 426 publications
(687 reference statements)
0
5
0
1
Order By: Relevance
“…Although much of that work involved increases in SEC rates caused by experimental increases in shoot density or root production, a few cases have shown that disturbance of existing vegetation can have a negative effect on elevation. Mortality of mangroves due to hurricanes or human activities, for example, can lead to elevation loss Stokes & Harris, 2015) or lowered resistance to erosion (McKee & Vervaeke, 2009). In mangrove systems in Honduras and Belize, the presence of mangrove roots was associated with high shear strength in both organic and mineral soils; disturbance of the vegetation or soils increased subsidence rates and decreased erosion resistance McKee & McGinnis, 2002;McKee & Vervaeke, 2009).…”
Section: Effect Of Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…Although much of that work involved increases in SEC rates caused by experimental increases in shoot density or root production, a few cases have shown that disturbance of existing vegetation can have a negative effect on elevation. Mortality of mangroves due to hurricanes or human activities, for example, can lead to elevation loss Stokes & Harris, 2015) or lowered resistance to erosion (McKee & Vervaeke, 2009). In mangrove systems in Honduras and Belize, the presence of mangrove roots was associated with high shear strength in both organic and mineral soils; disturbance of the vegetation or soils increased subsidence rates and decreased erosion resistance McKee & McGinnis, 2002;McKee & Vervaeke, 2009).…”
Section: Effect Of Disturbancementioning
confidence: 99%
“…Mortality of mangroves due to hurricanes or human activities, for example, can lead to elevation loss Stokes & Harris, 2015) or lowered resistance to erosion (McKee & Vervaeke, 2009). In mangrove systems in Honduras and Belize, the presence of mangrove roots was associated with high shear strength in both organic and mineral soils; disturbance of the vegetation or soils increased subsidence rates and decreased erosion resistance McKee & McGinnis, 2002;McKee & Vervaeke, 2009). In those cases, elevation loss was attributed to one or more factors: collapse of the living root matrix, a change in aboveground structures promoting sedimentation, or a decrease in organic matter contributions to soil volume.…”
Section: Effect Of Disturbancementioning
confidence: 99%
“…C = cave and galleries, F = reef flats, L = lagoon, M = mangrove, P = phanerogam meadows, R = reef. Díaz and Rützler, 2009;Valderrama and Zea, 2013;Rützler et al, 2014;Pérez et al, 2017), Toliara region harbours about half the specific richness, which confirms a little more the potential for new sponges to be inventoried and described in Madagascar and in the western Indian Ocean.…”
Section: Discussionmentioning
confidence: 85%
“…Sin embargo, Lluis-Riera (1972) reportó concentraciones de nitratos (0.20-1.29 μM) y de fosfatos (0.10-0.31 μM) en aguas cercanas a estos tres arrecifes entre 1967 y 1970. Estos niveles de fosfatos fueron más altos, en la mayoría de los casos, al valor encontrado por otros autores (~0.10 μM de fósforo reactivo soluble; Lapointe, 1999;Littler et al, 2009) como valor límite, a partir del cual los corales comienzan a ser desplazados por las macroalgas en los arrecifes. Lluis-Riera (1972) también encontró mayores concentraciones de nutrientes en el periodo lluvioso que en secas, pero en los años en que se realizó este estudio, las precipitaciones fueron pobres en la zona (López Deulofeu et al, 2005).…”
Section: Grupounclassified